THE NATURE DEPICTED IN JOHN LANCHESTER’S THE WALL (2019): AN ECOCRITICISM ANALYSIS - Muhlisin, Iqbatul; Rahayu, Mundi (Jurnal Pembelajaran Sastra, 2024)
During the last few decades, the condition of nature has been indisputably very dangerous and very poor. Intergovernmental Panel on Climate Change (IPCC) has reported that global warming will be happening on the earth, destroying the ice sheet that causes flooding in Miami, Dacca, Shanghai, Hong Kong, and other regions. Through that background, the concern on nature is increasingly important and it is addressed also in the literary work. This study specifically discusses the representation of nature in John Lanchester’s novel entitled ‘’The Wall”. The researchers focus on the question of what are environmental issues embedded in John Lanchester’s The Wall? This study applies an ecocriticism approach to achieve the objective. The study shows that environmental issues have been a serious concern that is represented in the novel. The issues are global warming, hunger, drowning, and pollution.